Upaya Peningkatan Pemahaman Masyarakat Desa Air Hitam Kecamatan Gebang Kabupaten Langkat Tentang Tindak Pidana Korupsi - Muhammad Yusuf; Andi Wijaya; Aulia Rahmadani (Medan Resource Center, 2021)
Corruption is a problem for this country. As an unusual crime, corruption must be eradicated in an unusual way. Eradication of corruption must be carried out as early as possible. Familiarizing anti-corruption behavior from an early age is expected to be a wave-breaker for anti-corruption in the future. The younger generation of the next generation, the leaders of the future leadership team, will play a strategic role in eradicating corruption. The chain of corruption that is already very strong must be broken by the younger generation. Therefore, the role of the younger generation in breaking the chain of corruption is very important. The problem with this activity is related to several things. First, the lack of understanding of the legal aspects of corruption. Second, the lack of understanding about corruption. Third, students are less aware of local corruption. There are basically three categories of ways to do this activity. The first is pre-activity which begins with the management process approving and validating the activity location. Second, the implementation of activities is carried out through questionnaires and lectures. Third, evaluation of activities.